A rapid survey of sheep production in the traditional sector of Debre Berhan, Ethiopian highlands - Agyemang, K.; Akalework, N.; Voorthuizen, A.; Anderson, F.M. (International Livestock Centre for Africa, 1985)
A rapid survey of livestock ownership patterns, flock demography and sheep productivity was undertaken on 120 flocks in four Peasant Associations. Sheep account for 64.7 per cent of the numbers of livestock owned. Mean flock size was 23.8 head and each flock was owned on average by 1.5 people. Flock sizes ranged from 2 to 83 and owners from 1 to 6. Females totalled 74.8 per cent of the flock, entire males 22.4 per cent and castrates 2.8 per cent. The ratio of breeding males to breeding females was 1:26, breeding females being about 49 per cent of the flock. Lambing occurred all the year round but 5.2 per cent of lambs were dropped in October and November resulting from conceptions in the early part of the main rains. Age at first lambing appeared to be older than in many other African areas. Lambing interval was about 350 days and 4.2 per cent of births resulted in twins. Total flock mortality was estimated at 6.5 per cent. The results are discussed in relation to ILCA's research on Debre Berhan station.